Trihalomethanes in liver pathology: Mitochondrial dysfunction and oxidative stress in the mouse. Issue 8 (9th January 2015) - Faustino‐Rocha, Ana I.; Rodrigues, D.; da Costa, R. Gil; Diniz, C.; Aragão, S.; Talhada, D.; Botelho, M.; Colaço, A.; Pires, M. J.; Peixoto, F.; Oliveira, P. A.
ABSTRACT: Trihalomethanes (THMs) are disinfection byproducts found in chlorinated water, and are associated with several different kinds of cancer in human populations and experimental animal models. Metabolism of THMs proceeds through enzymes such as GSTT1 and CYP2E1 and gives rise to reactive intermediates, which form the basis for their toxic activities. The aim of this study was to assess the mitochondrial dysfunction caused by THMs at low levels, and the resulting hepatic histological and biochemical changes in the mouse. Male ICR mice were administered with two THMs: dibromochloromethane (DBCM) and bromodichloromethane (BDCM); once daily, by gavage, to a total of four administrations. Animals were sacrificed four weeks after DBCM and BDCM administrations. Blood biochemistry was performed for alanine aminotransferase (ALT), aspartate aminotransferase (AST), alkaline phosphatase (ALP), total bilirubin (TB), albumin (Alb), total protein (TP), creatinine, and urea. Animals exposed to DBCM and BDCM showed elevated ALT and TB levels ( p  < 0.05) as compared with controls. Histological analysis confirmed the presence of vacuolar degenerescence and a multifocal necrotizing hepatitis in 33% of animals ( n  = 2). Mitochondrial analysis showed that THMs reduced mitochondrial bioenergetic activity (succinate dehydrogenase (SQR), cytochrome c oxidase (COX), and ATP synthase) and increased oxidative stress (glutathione S‐transferase (GST)) in hepatic tissues ( p  < 0.05). These results add detail to the current understanding of the mechanisms underlying THM‐induced toxicity, supporting the role of mitochondrial dysfunction and oxidative stress in liver toxicity caused by DBCM and BDCM. © 2015 Wiley Periodicals, Inc. Environ Toxicol 31: 1009–1016, 2016.